PENDIDIKAN KEWIRAUSAHAAN MELALUI PEMBINAAN KARAKTER BAGI SISWA SEKOLAH KEJURUAN DI KOTA SURAKARTA - Edhi Wasisto (ProBank, 2017)
The research aims to improve the knowledge, skills and motivation of entrepreneurship education for students and teachers in vocational schools (SMK) the city of Surakarta. The study consisted of three variables: (1) the intensity of the service model of entrepreneurship education; (2) entrepreneurial skills for students in Vocational High School .; (3) the effectiveness of services in entrepreneurship education through character education for students in Vocational High School. The research method is a survey, observation, interviews, questionnaires, documentation, and action (action research), giving the task to the subject of research and evaluation. The research location in the city of Surakarta. Given the technical constraints; limited funding and time of the study; as a test model specified the two schools; namely SMK SMK Bopkri 1 and 2. The research was conducted 6 months, beginning the month from April to October 2015. The quantitative data analysis using quantitative descriptive approach, while qualitative data using an interactive approach. Results: (1) obtained from the data base of potential Vocational High School. in the area of research related to the awareness and motivation of students in entrepreneurship; (2) obtained baseline prevalence of students who are interested in entrepreneurship education; (3) known to need assessment of the students who will participate in entrepreneurship education in schools; (4) can be prepared modules in entrepreneurship education material in Vocational High School; (5) can be arranged group accompanying teachers implementing entrepreneurship education in schools; (6) can be trained a number of 40 teachers accompanying the implementation of entrepreneurial skills education of students in the school; (7) can be produced prototype or tool entrepreneurship; (8) can be educated a number of 140 students in the field of entrepreneurial skills; (9) can be formed Productive Business Group (CTP) for students in the Vocational High School; (10) can be written journals of national terakriditasi; (11) can be written books on entrepreneurship education based character building for students at vocational schools. Keywords: Entrepreneurship education through character building vocational students